The Comparison of Balance of Dominant and Non-Dominant Legs in Soccer Players, Gymnasts, Swimmers and Basketball Players - sareh shahheidari; Aliasghar Norasteh; Hamid Mohebbi (Sport Sciences and Health Research)
The aim of this study was to compare static and dynamic balance of dominant and non-dominant legs in gymnasts, soccer players, basketball players and swimmers. For this purpose, 40 female athletes with 5 years of athletic experience (gymnasts n=10, age 14.50±0.31 years, height 155.20±7.75cm, weight 49.70±3.91 kg), soccer players (n=10, age 22.80±1.47 years, height 160.60±5.12 cm, weight 52.95±4.87 kg), swimmers (n=10, age 23.30±1.63 years, height 163.5±5.46 cm, weight 55.50±4.42 kg) and basketball players (n=10, age 21.60±1.07 years, height 165.5±6.75 cm, weight 57.43±6.27 kg) participated in this study as subjects. Static balance was assessed using the balance error scoring system (BESS) and dynamic balance was assessed using the star excursion balance test (SEBT). Data were analyzed by paired – sample t test (P? 0.05). Results showed no significant difference in static balance as well as dynamic balance between dominant and non-dominant legs (p>0.05) and it is not necessary to stand on the dominant leg to achieve the highest balance. This finding is particularly interesting for the clinicians who commonly use single leg postural control evaluations to assess an athletes’ progress in rehabilitation programs.